Improving Resightings of Two-Banded Plovers Flag Codes by using Digital Photo-Identification in Patagonia, Argentina - Hevia, Glenda Denise (2020)
Wildlife photography and digital photo-identification is a growing field that enhances many ecological features of avian population studies. Traditionally, binoculars and telescopes have been used to collect resighting data from marked birds, but the use of a non-invasive and complementary tool, such as a camera with telephoto lenses, has recently become a commonplace practice to identify flag codes on small banded shorebirds. We conducted surveys to resight marked Two-banded Plover (Charadrius falklandicus) adults between September and December 2017-2019 in northern Patagonia, Argentina, in order to explore site fidelity at their breeding grounds. Plovers were banded during the austral spring and summer using an orange flag with alphanumeric code placed on the tibia and a metal ring in the tarsus according to guidelines from the Pan American Shorebird Protocol. Banded plovers` detection and the ability to read flag codes in the field can be low when using binoculars and/or telescopes due to Patagonia´s characteristically strong wind conditions, which often limit field work activities. Hence, we used cameras with telephoto zoom lenses to increase accuracy when reading flag codes, allowing for banded plover´s individual identification. This fieldwork was possible due to the key participation of wildlife photographers, who contributed significantly with their time, expertise, and knowledge. In addition, several of the photographers belong to the Argentine Association of Nature Photographers (AFONA: www.afona.com.ar). Lastly, we strongly encourage the use of this technique as a complementary tool to improve banded bird´s detection and to verify flag codes.